1892 Ala. Laws 183 - (:unkn) unknown (My University, 1892)
Imposed $300 occupational tax on dealers of pistols, pistol cartridges, Bowie knives, and dirk knives, and clarified that cartridges that can be used in a pistol shall be deemed pistol cartridges.
Keywords: TAX - DEALERS